Partisipasi Politik Generasi Milenial pada Tantangan dan Peluang dalam Memperkuat Kewarganegaraan - Trisasabhilla, Maylisa; Prasanti, Talitha Nasywa; Zefron, Raisah Nabila; Ar Raudah, Diva; Fitri, Hairunnisa (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to describe and evaluate the participation of the millennial generation in politics, as well as highlight the challenges and opportunities they face in strengthening citizenship. The method used in creating this journal is the literature review and literature review method, involving analysis of data sourced from 12 journal articles in 2014-2023. The results of analysis and processing of research data show that there are several factors that influence the political participation of the millennial generation and opportunities that can strengthen citizenship, such as vision and mission, expectations for political leaders with high integrity and anti-corruption, high levels of political involvement. The Millennial generation also has several examples of opportunities to strengthen citizenship by participating in politics, such as by using social media which is currently widely used.